New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘Bush Blitz’ surveys of national reserves - Fagan-Jeffries, Erinn P.; Cooper, Steven J.b.; Austin, Andrew D. (Zootaxa, 2019)
The braconid subfamily Microgastrinae are ecologically important parasitoids of larval lepidopterans, but are poorly studied in many regions of the world. In this study, we focus on describing new species of microgastrine wasps, in part from specimens collected on six different ‘Bush Blitz’ surveys of regional reserves in South Australia and Tasmania. Ten species of Microgastrinae are described as new and DNA barcodes of the genes COI and wingless are provided: three species in the genus Choeras Mason: C. bushblitz Fagan-Jeffries & Austin sp. nov., C. parvoculus Fagan-Jeffries & Austin sp. nov., and C. zygon Fagan-Jeffries & Austin sp. nov.; six species in the genus Dolichogenidea Viereck: D. bonbonensis Fagan-Jeffries & Austin sp. nov., D. brabyi Fagan-Jeffries & Austin sp. nov., D. forrestae Fagan-Jeffries & Austin sp. nov., D. garytaylori Fagan-Jeffries & Austin sp. nov., D. kelleri Fagan-Jeffries & Austin sp. nov., and D. lobesiae Fagan-Jeffries & Austin sp. nov.; and one species from the genus Sathon Mason: S. oreo Fagan-Jeffries & Austin sp. nov. These new species represent just a small fraction of the potential of ‘Bush Blitz’ surveys in regional Australia, which provide DNA-quality material allowing an integrative taxonomic approach and offer a window into the biodiversity of some of the least studied areas of the continent.